1995
DOI: 10.1029/94jb02643
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism of the Upper Cretaceous strata of Mount Tatlow: Evidence for 3000 km of northward displacement of the eastern Coast Belt, British Columbia

Abstract: This study contributes the first palcomagnetic data from dated Cretaceous units of the Coast Belt (51.3øN, 123.8øW) in which palcohorizontal bedding surfaces can be identified with certainty. We sampled 38 sites through a 1.5-km stratigraphic interval of Cenomanian Silverquick sedimentary strata and Cenomanian to Campanian Powell Creek volcanics in the Tatlow syncline in the Tyaughton-Methow Basin. Magnetizations at 21 sites have high unblocking temperatures (TUB) and pass the tilt test (precision k = 5 before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 46 publications
(12 reference statements)
5
81
1
Order By: Relevance
“…[4] Discordant paleomagnetic directions have also been observed in Cretaceous sedimentary and volcanic rocks of the northern North American Cordillera [Wynne et al, 1995;Ward et al, 1997]. Some workers have concluded that the consistently shallow paleomagnetic inclinations confirm the transport interpretation of discordant paleomagnetic directions from the plutonic rocks.…”
Section: Introductionmentioning
confidence: 58%
“…[4] Discordant paleomagnetic directions have also been observed in Cretaceous sedimentary and volcanic rocks of the northern North American Cordillera [Wynne et al, 1995;Ward et al, 1997]. Some workers have concluded that the consistently shallow paleomagnetic inclinations confirm the transport interpretation of discordant paleomagnetic directions from the plutonic rocks.…”
Section: Introductionmentioning
confidence: 58%
“…The extent of Cretaceous to early Paleogene displacement on the Pasayten fault is more controversial (e.g., Lawrence 1978;Butler et al 1989;Hurlow 1993;Wynne et al 1995;Wyld et al 2006). The Pasayten fault has been proposed as the locus for large-scale dextral translation; values of displacement on the Pasayten fault range from <1000 km (e.g., Butler et al 1989;Kodama and Ward 2001) to >3000 km of displacement (e.g., Wynne et al 1995;Irving et al 1996;Ward et al 1997).…”
Section: Tectonic Historymentioning
confidence: 99%
“…Controversial paleomagnetic data suggest that the basin (and the associated Insular superterrane) may have undergone large-scale northward latitudinal translation (e.g., Beck et al, 1981;Wynne et al, 1995;Irving et al, 1996;Enkin et al, 2003), potentially originating as far south as central Mexico (ϳ25ЊN). Conversely, structural data, basin reconstructions, timing constraints, and alternate interpretations of paleomagnetic data indicate that the basin developed at or near its current latitude and perhaps was trapped east of the Insular superterrane during sinistral (i.e., southward) translation in Cretaceous time (e.g., Butler et al, 1989;Miller et al, 1993;Umhoefer and Miller, 1996;Kodama and Ward, 2001).…”
Section: Paleogeographic Implicationsmentioning
confidence: 99%
“…Paleomagnetic data from the Intermontane and Insular superterranes have been interpreted to suggest that the modern Pasayten fault is coincident with the principal locus of (1) as much as 3000 km of dextral translation that occurred between 85 and 50 Ma (e.g., Wynne et al, 1995;Irving et al, 1996), or (2) less than 1500 km of translation (e.g., Butler et al, 1989;Kodama and Ward, 2001). Therefore, rocks on opposite sides of the modern Pasayten fault may or may not have been in geographic proximity in the Late Cretaceous, and strata of the Methow/Methow-Tyaughton basin may be cut off from their eastern source.…”
Section: Structural Settingmentioning
confidence: 99%